2015
DOI: 10.1007/s12291-015-0541-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetics of Obesity

Abstract: Numerous classical genetic studies have proved that genes are contributory factors for obesity. Genes are directly responsible for obesity associated disorders such as Bardet-Biedl and Prader-Willi syndromes. However, both genes as well as environment are associated with obesity in the general population. Genetic epidemiological approaches, particularly genome-wide association studies, have unraveled many genes which play important roles in human obesity. Elucidation of their biological functions can be very u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 102 publications
2
19
0
2
Order By: Relevance
“…In previous research (Trakovická et al, 2015;Candráková, Trakovická, 2016), we also found connection between polymorphisms in the LEP (G2548A), LEPR (Gln223Arg) and GHR (171T/C) genes and BMI level. But mainly due to the limited sample and polygenic character of evaluated traits further research is needed.…”
Section: Molecular-genetic Analysis Of Gene Fto Rs1121980supporting
confidence: 71%
See 1 more Smart Citation
“…In previous research (Trakovická et al, 2015;Candráková, Trakovická, 2016), we also found connection between polymorphisms in the LEP (G2548A), LEPR (Gln223Arg) and GHR (171T/C) genes and BMI level. But mainly due to the limited sample and polygenic character of evaluated traits further research is needed.…”
Section: Molecular-genetic Analysis Of Gene Fto Rs1121980supporting
confidence: 71%
“…Gene identification efforts using the genetic studies have provided a more broad aspect to understand the biological mechanisms involved in the development of obesity and this information can be important not only for scientists and clinicians but for a general population too (Srivastava A., Srivastava N., Mittal, 2015). Zhang et al (2010) confirmed the association of common variants of FTO gene with ''body fatness'' measures in an isolated island population.…”
Section: Introductionmentioning
confidence: 92%
“…Obesity is a chronic relapsing, stigmatized neurochemical disease that is more prevalent in developing and developed countries and leading to much comorbidities. 1 Obesity, which is associated with serious moralities including a high incidence of type 2 diabetes, hyperlipidemia, hypercholestrolemia, cardiovascular disease, osteoarthritis, and many more diseases. [1][2] Obesity is a disorder not a disease, but, it has been recognized as a chronic disease by National Institute of health consensus conference in 1985 due to the increasing prevalence and associated risks.…”
Section: Introductionmentioning
confidence: 99%
“…1 Obesity, which is associated with serious moralities including a high incidence of type 2 diabetes, hyperlipidemia, hypercholestrolemia, cardiovascular disease, osteoarthritis, and many more diseases. [1][2] Obesity is a disorder not a disease, but, it has been recognized as a chronic disease by National Institute of health consensus conference in 1985 due to the increasing prevalence and associated risks. 2 This situation currently prevailing widely, anti-obesity drugs expanding rapidly in the market, but drugs are sparse in relation to need.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that substitution of different heterocyclic moieties at 2 or 3 position of quinazolinone nucleus modulates the antiinflammatory activity. A large numbers of azetidinones, [3,4] thiazolidinones [5,6] and oxadiazoles [7][8][9] were reported to possess anti-inflammatory activity.…”
Section: Introductionmentioning
confidence: 99%